Sexual harassment and abuse; disclosure and awareness of report- and support resources in Norwegian sport- and non-sport high schools: a prospective exploratory study - Sølvberg, Nina; Torstveit, Monica Klungland; Mountjoy, Margo; Rosenvinge, Jan H.; Pettersen, Gunn; Sundgot-Borgen, Jorunn (Frontiers in Psychology, 2023)
Purpose: To examine high school students’ disclosure of sexual harassment and abuse (SHA), and awareness of reporting systems and support mechanisms in school among students, leaders, and coaches. Method: Norwegian 17-year-old high school elite athletes (n=630), recreational athletes (n=307), and reference students (n=263) responded to an online questionnaire at two measurement points, one year apart (T1 and T2). Leaders and coaches (n=249) at the participating high schools responded to an adapted version of the questionnaire at T1. Data were analyzed using ANOVA or Welch test, Pearson Chi-Square test, and McNemar test. Results: In total, 11.4% and 34.0% of the adolescents were aware of reporting systems and support mechanisms, respectively, in their schools. Nearly all the leaders, and half of the coaches were aware of these resources. Among the adolescents with lifetime experience of SHA, 20.1% had disclosed their experiences to someone. Girls disclosed more frequently than boys. The elite- and recreational athletes disclosed less often compared with the reference students. A negative change from T1 to T2 was found in disclosure of SHA and awareness of support mechanisms. At T2, 6.5% of the adolescents reported that their school had implemented measures against SHA during the last 12 months. Conclusions: The results emphasize a need for institutional effort to improve information about available report- and support resources and increase the relevance of use of such systems for adolescents.